A method for producing a low-lead deposited ir-ta oxide coating anode

CN116856018BActive Publication Date: 2026-11-03XIAN TAIJIN NEW ENERGY & MATERIALS SCI TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310879887.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-07-18
Publication Date
2026-11-03
Estimated Expiration
2043-07-18

AI Technical Summary

Technical Problem

In the existing electrolytic copper foil production process, the deposition of lead compounds on the anode surface leads to uneven distribution of electric field lines, affecting the uniformity of the copper foil and the stability of the anode, resulting in anode failure.

Method used

A method for preparing a low-lead deposited Ir-Ta oxide coating anode was adopted. Water was added to the active solution to suppress the deposition and conversion rate of lead ions on the anode surface. A uniform Ir-Ta oxide coating was prepared by sol-gel method. The titanium substrate surface was then subjected to sandblasting, acid washing, etching and other treatments. The sol-gel method was used to uniformly mix metallic iridium salt and tantalum salt to form a uniform oxide coating.

Benefits of technology

It inhibits the formation of lead compounds on the anode surface, improves the uniformity of copper foil, extends the service life of the anode, reduces the oxygen evolution potential, and reduces the occurrence of surface cracks.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116856018B_ABST
    Figure CN116856018B_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of electrolytic copper foil and relates to a preparation method of a low-lead deposition Ir-Ta oxide coating anode, which comprises the following steps: performing surface pretreatment on a titanium base material, using a sol-gel method to configure an active liquid, and sintering the active liquid by brushing. The application adds water when preparing the active liquid, thereby inhibiting the formation of iridium dioxide on the surface of the anode, reducing the occurrence of cracks on the surface of the anode, inhibiting the generation of lead compounds on the surface of the anode, improving the uniformity of the copper foil, and prolonging the service life of the anode.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of electrolytic copper foil technology, and relates to coated anodes for electrolytic copper foil, and more particularly to a method for preparing a low-lead deposited Ir-Ta oxide coated anode. Background Technology

[0002] The rapid development of 5G, the internet, and new energy vehicle industries has further expanded the electrolytic copper foil industry. This has led to increasingly stringent requirements for the iridium-tantalum anode, a crucial component in the electrolytic copper foil production process, primarily in terms of anode stability and electrochemical activity. However, the electroplating solution in the entire electroplating system may contain Pb. 2+ This leads to the formation of an uneven lead compound scale layer on the anode surface, resulting in uneven distribution of electric field lines between the anode and cathode. This affects the uniformity of copper foil production at the cathode, ultimately causing the anode to be deemed as faulty.

[0003] This invention designs a coating that can inhibit the deposition and transformation of lead compounds on the anode, improve the uniformity of copper foil, and extend the service life of the anode. Summary of the Invention

[0004] To address the shortcomings of existing technologies, the present invention aims to provide a method for preparing a low-lead deposited Ir-Ta oxide coated anode. By adding water, the deposition and conversion rate of lead ions in the electrolyte on the anode surface is suppressed, the formation of lead compounds on the anode surface is inhibited, the uniformity of the copper foil is improved, and the service life of the anode is extended.

[0005] To achieve the above objectives, the present invention provides the following technical solution:

[0006] A method for preparing a low-lead deposited Ir-Ta oxide coated anode includes the following steps:

[0007] (1) Surface pretreatment of titanium substrate;

[0008] (2) Preparation of active solution: Measure an organic solvent and heat it. Add the chelating agent and additive in sequence and mix until completely dissolved. Then add the tantalum source and iridium source and mix well. Finally, slowly add water dropwise and mix well to form an active solution. The organic solvent is any one or a combination of two or more of polyethylene glycol, ethylene glycol, n-butanol, ethylene oxide, and triethanolamine. The chelating agent is any one or a combination of two or more of hydrochloric acid, acetic acid, ammonia, and EDTA. The additive is any one or a combination of two or more of acetylacetone, polyvinyl alcohol, and dimethylformamide.

[0009] (3) The active liquid prepared in step (2) is applied to the surface of the titanium substrate after treatment in step (1) and then sintered.

[0010] Furthermore, the pretreatment in step (1) includes sandblasting, pickling, cleaning, and drying.

[0011] Furthermore, in step (2), the weight of iridium ions in the active solution accounts for 50-90% of the total metal ion mass, the weight of tantalum ions accounts for 10-50% of the total metal ion mass, and the total metal ion concentration of the solution is 0.1-0.3 mol / L.

[0012] Furthermore, in step (2), the mass concentration of the chelating agent added to the active liquid is 0.2-0.8 g / ml, and the mass concentration of the additive added is 0.1-0.3 g / ml.

[0013] Furthermore, in step (2), the volume ratio of water to organic solvent added to the active solution is (1 / 3-3):1.

[0014] Furthermore, the tantalum source is any one of tantalum pentachloride n-butanol solution, tantalum butanediol, and tantalum ethoxide.

[0015] Furthermore, the iridium source is any one of chloroiridium acid, iridium trichloride, and bromoiridium acid.

[0016] Furthermore, the water is deionized water.

[0017] Furthermore, step (3) specifically includes the following steps:

[0018] 3.1) Dry the titanium substrate coated with the active liquid at 90-120℃ for 10-20 minutes;

[0019] 3.2) Sinter the titanium substrate treated in step 3.1) directly at 480-500℃ for 10-30 minutes. After cooling to room temperature, apply the next coating. Repeat step 3.1) until all the coating liquid is used up.

[0020] 3.3) The titanium substrate coated in step 3.2) is kept at 480-500℃ for 1 hour to prepare a novel Ir-Ta system oxide coating anode.

[0021] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0022] 1. The present invention provides a method for preparing a low-lead deposited Ir-Ta oxide coated anode. By adding water to the active liquid, the introduction of water reduces the oxygen evolution potential of the anode and changes the solvent decomposition temperature, thereby inhibiting the formation of iridium dioxide on the anode surface, reducing the occurrence of surface cracks, reducing the deposition and conversion rate of lead ions in the electrolyte on the anode surface, inhibiting the formation of lead compounds on the anode surface, improving the uniformity of copper foil, and extending the service life of the anode.

[0023] 2. The present invention provides a method for preparing a low-lead deposited Ir-Ta oxide coated anode. In the preparation of the iridium-tantalum coated anode, the active solution is prepared by sol-gel method, which uniformly mixes the metallic iridium salt and tantalum salt, and the final anode surface has uniform composition. Attached Figure Description

[0024] Figure 1 This is a scanning electron microscope image of the Ir-Ta oxide anode prepared in Example 1 of the present invention.

[0025] Figure 2 This is a scanning electron microscope image of the Ir-Ta oxide anode prepared in Example 2 of the present invention.

[0026] Figure 3 This is a scanning electron microscope image of the Ir-Ta oxide anode prepared in Example 3 of the present invention.

[0027] Figure 4 This is a scanning electron microscope image of the Ir-Ta oxide anode prepared in Comparative Example 1 of this invention.

[0028] Figure 5 This is a scanning electron microscope image of the Ir-Ta oxide anode prepared in Comparative Example 2 of this invention.

[0029] Figure 6 This is a comparison of the anodic polarization curves of Ir-Ta oxides prepared in the embodiments and comparative examples of the present invention.

[0030] Among them, the above Figure 1-5 The magnification factor is the same, 1000X. Detailed Implementation

[0031] The present invention will be further described in detail below with reference to the accompanying drawings and embodiments:

[0032] This invention provides a method for preparing a low-lead deposited Ir-Ta oxide coated anode, the method comprising the following steps:

[0033] (1) Titanium substrate pretreatment: The surface of the titanium substrate is subjected to sandblasting, pickling, etching, drying and other treatments;

[0034] (2) Preparation of the active solution: Measure the organic solvent and place it on a temperature-adjustable stirrer. Add the chelating agent (0.2-0.8 g / ml) and the additive (0.1-0.3 g / ml) sequentially, stirring until completely dissolved. Then add the tantalum source and iridium source and continue stirring for 30 minutes. The iridium ion weight should account for 50-90% of the total metal ion weight, and the tantalum ion weight should account for 10-50% of the total metal ion weight. The total metal ion concentration of the solution should be 0.1-0.3 mol / L. Finally, slowly add water dropwise until all water is added, mix well to form the active solution, and add... The volume ratio of water to organic solvent is (1 / 3-3):1; the organic solvent is any one or a combination of two or more of polyethylene glycol, ethylene glycol, n-butanol, ethylene oxide, and triethanolamine; the chelating agent is any one or a combination of two or more of hydrochloric acid, acetic acid, ammonia, and EDTA; the additive is any one or a combination of two or more of acetylacetone, polyvinyl alcohol, and dimethylformamide; the tantalum source is any one of tantalum pentachloride n-butanol solution, tantalum butanediol, and tantalum ethoxide; the iridium source is any one of chloroiridic acid, iridium trichloride, and bromoiridic acid; and the water is deionized water.

[0035] (3) Sintering: The active liquid prepared in step (2) is evenly coated onto the titanium substrate treated in step (1), and placed in a chain sintering furnace at 90-120℃ for drying for 10-20 minutes; then it is directly placed at 480-500℃ for sintering for 10-30 minutes. After cooling to room temperature, the next coating is applied. The above steps are repeated until all the coating liquid is used up. Finally, the substrate is kept at 480-500℃ in a chain sintering furnace for 1 hour to prepare a low-lead deposited Ir-Ta oxide coating anode.

[0036] Example 1

[0037] This embodiment provides a method for preparing a low-lead deposited Ir-Ta oxide coated anode, the method specifically including:

[0038] (1) Titanium substrate pretreatment: The surface of the titanium substrate is subjected to sandblasting, pickling, etching, drying and other treatments;

[0039] (2) Preparation of active solution: Measure 15 ml of polyethylene glycol and place it on a temperature-adjustable stirrer. Add 12 g of chelating agent EDTA and 4.5 g of additive polyvinyl alcohol in sequence. Stir at 60°C until completely dissolved. Then add tantalum chloride n-butanol solution and chloroiridium acid and continue stirring for 30 min. The weight of iridium ions accounts for 70% of the total metal ion mass, and the weight of tantalum ions accounts for 30% of the total metal ion mass. The total metal ion concentration of the solution is 0.2 mol / L. Finally, slowly add 5 ml of deionized water. The ratio of the volume of water to the volume of organic solvent is 1:3. Mix well to form active solution.

[0040] (3) Sintering: The prepared active liquid was uniformly coated onto the treated titanium substrate and dried in a chain sintering furnace at 100℃ for 15 min. Then, it was sintered directly at 490℃ for 20 min. After cooling to room temperature, the next coating was applied. The above steps were repeated until all the coating liquid was used up. Finally, the substrate was kept at 490℃ in the chain furnace for 1 h to prepare a novel Ir-Ta system oxide coating anode. The scanning electron microscope image is shown below. Figure 1 .

[0041] Example 2

[0042] This embodiment provides a method for preparing a low-lead deposited Ir-Ta oxide coated anode, the method specifically including:

[0043] (1) Titanium substrate pretreatment: The surface of the titanium substrate is subjected to sandblasting, pickling, etching, drying and other treatments;

[0044] (2) Preparation of active solution: Measure 10 ml of polyethylene glycol and place it on a temperature-adjustable stirrer. Add 2 g of chelating agent EDTA and 1 g of additive polyvinyl alcohol in sequence. Stir at 60°C until completely dissolved. Then add tantalum chloride n-butanol solution and chloroiridium acid and continue stirring for 30 min. The weight of iridium ions accounts for 70% of the total metal ion mass, and the weight of tantalum ions accounts for 30% of the total metal ion mass. The total metal ion concentration of the solution is 0.2 mol / L. Finally, slowly add 10 ml of deionized water. The ratio of the volume of water added to the volume of organic solvent is 1:1. Mix well to form active solution.

[0045] (3) Sintering: The prepared active liquid was uniformly coated onto the treated titanium substrate and dried in a chain sintering furnace at 100℃ for 15 min. Then, it was sintered directly at 490℃ for 20 min. After cooling to room temperature, the next coating was applied. The above steps were repeated until all the coating liquid was used up. Finally, the substrate was kept at 490℃ in the chain furnace for 1 h to prepare a novel Ir-Ta system oxide coating anode. The scanning electron microscope image is shown below. Figure 2 .

[0046] Example 3

[0047] This embodiment provides a method for preparing a low-lead deposited Ir-Ta oxide coated anode, the method specifically including:

[0048] (1) Titanium substrate pretreatment: The surface of the titanium substrate is subjected to sandblasting, pickling, etching, drying and other treatments;

[0049] (2) Preparation of active solution: Measure 5 ml of polyethylene glycol and place it on a temperature-adjustable stirrer. Add 2 g of chelating agent EDTA and 0.5 g of additive polyvinyl alcohol in sequence. Stir at 60°C until completely dissolved. Then add tantalum chloride n-butanol solution and chloroiridium acid and continue stirring for 30 min. The weight of iridium ions accounts for 70% of the total metal ion mass, and the weight of tantalum ions accounts for 30% of the total metal ion mass. The total metal ion concentration of the solution is 0.2 mol / L. Finally, slowly add 15 ml of deionized water. The ratio of the volume of water to the volume of organic solvent is 3:1. Mix well to form active solution.

[0050] (3) Sintering: The prepared active liquid was uniformly coated onto the treated titanium substrate and dried in a chain sintering furnace at 100℃ for 15 min. Then, it was sintered directly at 490℃ for 20 min. After cooling to room temperature, the next coating was applied. The above steps were repeated until all the coating liquid was used up. Finally, the substrate was kept at 490℃ in the chain furnace for 1 h to prepare a novel Ir-Ta system oxide coating anode. The scanning electron microscope image is shown below. Figure 3 .

[0051] Comparative Example 1

[0052] This comparative example provides a method for preparing an Ir-Ta composite oxide coated anode, the method specifically including:

[0053] (1) Titanium substrate pretreatment: The surface of the titanium substrate is treated by degreasing, sandblasting, hot shaping, pickling and other processes;

[0054] (2) Preparation of active solution: Weigh chloroiridic acid and dissolve it in n-butanol solvent, with a metal ion concentration of 0.2 mol / L. Stir at room temperature until completely dissolved to form solution A; Weigh tantalum pentachloride n-butanol solution and dissolve it in n-butanol solvent, with a metal ion concentration of 0.2 mol / L. Stir at room temperature until completely dissolved to form solution B;

[0055] Mix solutions A and B in a molar ratio of Ir:Ta = 7:3 to form active solution D, and store it for later use.

[0056] (3) Sintering: The prepared active liquid D is uniformly coated onto the titanium substrate to ensure even diffusion. The substrate is then placed in an 80°C oven to allow the solvent to evaporate completely. Next, it is sintered in a 500°C muffle furnace for 15 minutes. After removal, it is allowed to cool naturally to room temperature. This process is repeated until the coating is completely applied. Finally, the coated titanium substrate is kept in a 500°C muffle furnace for 1 hour, then removed and allowed to cool naturally to room temperature. See the scanning electron microscope image for details. Figure 4 .

[0057] Comparative Example 2

[0058] This comparative example provides a method for preparing an anode with a low-lead deposited Ir-Ta oxide coating, the method specifically including:

[0059] (1) Titanium substrate pretreatment: The surface of the titanium substrate is subjected to sandblasting, pickling, etching, drying and other treatments;

[0060] (2) Preparation of active solution: Measure 20 ml of polyethylene glycol and place it on a temperature-adjustable stirrer. Add 10 g of chelating agent EDTA and 2 g of additive polyvinyl alcohol in sequence. Stir at 60°C until completely dissolved. Then add tantalum chloride n-butanol solution and chloroiridium acid and continue stirring for 30 min. The weight of iridium ions accounts for 70% of the total metal ion mass, and the weight of tantalum ions accounts for 30% of the total metal ion mass. The total metal ion concentration of the solution is 0.2 mol / L. Mix well to form active solution.

[0061] (3) Sintering: The prepared active liquid was uniformly coated onto the treated titanium substrate and dried in a chain sintering furnace at 100℃ for 15 min. Then, it was sintered directly at 490℃ for 20 min. After cooling to room temperature, the next coating was applied. The above steps were repeated until all the coating liquid was used up. Finally, the substrate was kept at 490℃ in the chain furnace for 1 h to prepare a novel Ir-Ta system oxide coating anode. The scanning electron microscope image is shown below. Figure 5 .

[0062] Electrochemical performance tests were conducted in a 0.5 mol / L sulfuric acid solution, such as... Figure 6 The figure shown is a comparison of the anodic polarization curves of Examples 1-3 and Comparative Examples 1 and 2.

[0063] Add 300 ppm of lead nitrate to a 1 mol / L sulfuric acid solution and place it in a 50°C constant temperature stirred water bath. Stir at 500 r / min and perform lead deposition experiment on the prepared anode for 3 days.

[0064] The mass changes of Ir-Ta oxide coatings before and after anodic lead deposition prepared using the methods provided in Examples 1-3 and Comparative Examples 1 and 2 are shown in the table below:

[0065] Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Mass before lead precipitation / g 0.913 0.917 0.876 0.930 0.862 Mass after lead precipitation / g 0.932 0.935 0.892 0.965 0.890

[0066] In summary, this invention utilizes a sol-gel method to prepare the active solution. By adding different amounts of aqueous solvent to the active solution, Ir-Ta oxide-coated anodes were prepared, and their electrochemical performance was tested. The introduction of aqueous solvent lowered the oxygen evolution potential of the anode, altered the solvent decomposition temperature, inhibited the formation of iridium dioxide on the anode surface, reduced the occurrence of surface cracks, decreased the deposition and conversion rate of lead ions in the electrolyte on the anode surface, and suppressed the formation of lead compounds on the anode surface.

[0067] The above description is merely a specific embodiment of the present invention and is only used to illustrate the present invention, enabling those skilled in the art to understand or implement the present invention, and is not intended to limit the present invention. Those skilled in the art can make various changes and modifications without departing from the spirit and scope of the present invention, and all equivalent technical solutions made are also within the protection scope of the present invention.

Claims

1. A method for preparing a low-lead deposited Ir-Ta oxide coated anode, characterized in that, Includes the following steps: (1) Surface pretreatment of the titanium substrate; (2) Preparation of active solution: Measure organic solvent and heat it. Add chelating agent and additive in sequence and mix until completely dissolved. Then add tantalum source and iridium source and mix well. Finally, slowly add water dropwise and mix well to form active solution. The organic solvent is any one or a combination of two or more of polyethylene glycol, ethylene glycol, n-butanol, ethylene oxide and triethanolamine. The chelating agent is any one or a combination of two or more of hydrochloric acid, acetic acid, ammonia water and EDTA. The additive is any one or a combination of two or more of acetylacetone, polyvinyl alcohol and dimethylformamide. In step (2), the weight of iridium ions in the active solution accounts for 50-90% of the total metal ion mass, the weight of tantalum ions accounts for 10-50% of the total metal ion mass, and the total metal ion concentration of the solution is 0.1-0.3 mol / L. In step (2), the mass concentration of the chelating agent added to the active solution is 0.2-0.8 g / ml, and the mass concentration of the additive added is 0.1-0.3 g / ml. In step (2), the volume ratio of water to organic solvent added to the active solution is (1 / 3-3):

1. (3) The active liquid prepared in step (2) is applied to the surface of the titanium substrate after treatment in step (1) and then sintered.

2. The method for preparing a low-lead deposited Ir-Ta oxide coated anode according to claim 1, characterized in that, The pretreatment in step (1) includes sandblasting, pickling, cleaning, and drying.

3. The method for preparing a low-lead deposited Ir-Ta oxide coated anode according to claim 1, characterized in that, The tantalum source is any one of tantalum pentachloride n-butanol solution, tantalum butanediol, or tantalum ethoxide.

4. The method for preparing a low-lead deposited Ir-Ta oxide coated anode according to claim 1, characterized in that, The iridium source is any one of chloroiridium acid, iridium trichloride, and bromoiridium acid.

5. The method for preparing a low-lead deposited Ir-Ta oxide coated anode according to claim 1, characterized in that, The water is deionized water.

6. The method for preparing a low-lead deposited Ir-Ta oxide coated anode according to claim 1, characterized in that, Step (3) specifically includes the following steps: 3.1) Dry the titanium substrate coated with the active liquid at 90-120℃ for 10-20 minutes; 3.2) The titanium substrate treated in step 3.1) is sintered directly at 480-500℃ for 10-30 minutes. After cooling to room temperature, the next coating is applied. Repeat step 3.1) until all the coating liquid is used up. 3.3) The titanium substrate coated in step 3.2) is kept at 480-500℃ for 1 hour to prepare a novel Ir-Ta system oxide coating anode.

Citation Information

Patent Citations

  • Manufacturing process of electrodes for electrolysis

    CN101550557A

  • Preparation method of coating anode plate

    CN109706513A